A Mobile Application to Guide Hajj Pilgrims - Anad, Mohammed Morad (2009)
There are a lot of pilgrims, when they perform the duty, they should face a lot of challenges. With the popularization of mobile, their problems are hoped to be solved by the Mobile Service to Perform Hajj, which is proposed in this study. In this system, the advice and guidance is provided to the pilgrims. The information of Hajj steps, hotels, streets and restaurants can be got from this system by using mobile phones. This study adopts the waterfall methodology to develop this system. With the help from this Mobile service to perform Hajj, it is hoped that pilgrims can find the information they need easily and perform the hajj successfully.